Well, I bet you want your answer right away! So here it is.
<span>Given <span>f (x) = 3x + 2</span> and <span>g(x) = 4 – 5x</span>, find <span>(f + g)(x), (f – g)(x), (f × g)(x)</span>, and <span>(f / g)(x)</span>.</span>
To find the answers, all I have to do is apply the operations (plus, minus, times, and divide) that they tell me to, in the order that they tell me to.
(f + g)(x) = f (x) + g(x)
= [3x + 2] + [4 – 5x]
= 3x + 2 + 4 – 5x
= 3x – 5x + 2 + 4
= –2x + 6
(f – g)(x) = f (x) – g(x)
= [3x + 2] – [4 – 5x]
= 3x + 2 – 4 + 5x
= 3x + 5x + 2 – 4
= 8x – 2
(f × g)(x) = [f (x)][g(x)]
= (3x + 2)(4 – 5x)
= 12x + 8 – 15x2 – 10x
= –15x2 + 2x + 8
<span>\left(\small{\dfrac{f}{g}}\right)(x) = \small{\dfrac{f(x)}{g(x)}}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>g(x)</span></span><span><span>f(x)</span></span><span></span></span></span></span><span>= \small{\dfrac{3x+2}{4-5x}}<span>=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span></span></span></span></span>
My answer is the neat listing of each of my results, clearly labelled as to which is which.
( f + g ) (x) = –2x + 6
( f – g ) (x) = 8x – 2
( f × g ) (x) = –15x2 + 2x + 8
<span>\mathbf{\color{purple}{ \left(\small{\dfrac{\mathit{f}}{\mathit{g}}}\right)(\mathit{x}) = \small{\dfrac{3\mathit{x} + 2}{4 - 5\mathit{x}}} }}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span>
Hope I helped! :) If I did not help that's okay.
-Duolingo
</span></span></span></span>
First check whether the point (-6,8) is the solution to any of the equations. To check, just plug in the x and y values of the points into the equation and see if they give you a true statement.
5(-6)+3(8)=-6
-30+24=-6
-6=-6
That's a true statement so the point is the solution to the first equation.
2(-6)+(8)=-4
-12+8=-4
-4=-4
It is a true statement so the point is a solution for both equations
There are no other solution because lines can only intersect in one or infinite points, but that is only if they are the same lines, which is not true in this circumstance.
A. It is the only solution to the set.
Hope this helps.
Rewrite using the formula for the standard form
The answer is y-4x^2 + 12x + 9
Answer:
YZ = 18.4 in
Step-by-step explanation:
The midsegment YZ is half the length of the third side VX , then
YZ =
× 36.4 = 18.2
Answer:
ok so the first one is
1200x+2000
the second one is
1000x+3000
month 1.
a.3200
b.4000
month 2.
a.4400
b.5000
month 3.
a.5600
b.6000
month 4.
a. 6800
b. 7000
month 5.
a. 8000
b. 8000
They would equal out at 8000 in month 5